Model Pengelolaan Pasokan dan Risiko Mutu Rantai Pasok Kopi Gayo - Rachman Jaya (Agricultural Faculty, 2013)
A factual problem in the coffee agroindustry at Gayo highlands Aceh Province is the utilization requirement of raw material supply and quality which inaccordance with procesor demand. The purposes of the study are to develop model of supply utilization and to determine alternative of risk management quality of Gayo coffee in the agroindustry at the Gayo Highlands of Aceh Province. Requirement of utilization supply solved by ARIMA technique, risk management quality by Multi Expert Multi Criteria Decison Making, aggregation criteria with OWA. The result of the study shows that utilization rate was 4.052 tons/years. The alternatives of quality risk management are improvement of human resources, transportation system and drying technology applications with high assessment criteria so the agroindustry must focus on this dimension.